3F.004 Occupational heat stress and economic burden: evidence for workplace heat management policies. (14th March 2021) - Borg, Matthew; Bi, Peng; Xiang, Jianjun; Anikeeva, Olga
Abstract : Background: The adverse effects of heat on workers' health and work productivity are well documented. However, the resultant economic consequences are less understood. This review aims to summarise the retrospective and future economic burden of workplace heat exposure. Methods: Literature was searched from database inception to August 2019 using PubMed, Scopus and Embase. Papers were limited to original human studies investigating costs from occupational heat stress. Results: This review included 14 studies. 12 studies estimated costs secondary to decreased labour productivity. Predicted global costs from lost worktime were US 311 billion in 2010 (≈0.5% of GDP), 2.5 trillion in 2030 (>1% of GDP) and up to 4.0% of GDP by 2100, with additional expenses after considering decreased work efficiency. Three studies estimated healthcare expenses from occupational illnesses/injuries due to heat with averaged annual costs exceeding 1 million in Spain and Guangzhou and 250, 000 in Adelaide. Developing countries and countries with warmer climates had greater GDP losses. Some studies investigated and observed greater costs per worker in outdoor industries, amongst males, those aged 25 to 44, and medium-sized businesses. Conclusions: Estimated global expenses are substantial. Climate change mitigation and adaption can minimise most future costs. Further research exploring the relationship between occupational heat stress and costs, expenses from decreased work efficiency and healthcare, and costs stratified by demographics factors is warranted. Learning Outcomes: Analysing heat-attributable occupational costs may guide the development of workplace heat management policies and global warming strategies. Responding to climate change is crucial to minimise future economic burden